Columbia / New York: The Ruins of the Civil War - Thomas Constantinesco (Transatlantica)
This essay explores the political aesthetics of visual and textual representations of ruins following episodes of urban destruction during the Civil War. Although ruins were long held to be lacking in the nineteenth-century US landscape—and their absence deemed a sign of America’s newness—ruins were ubiquitous throughout the nation, in particular in its growing urban centres. These antebellum ruins spoke to America’s uncanny historicity, spelling out its premature growth as well as the risk of its untimely extinction. Their presence, however transient, thus provided Americans with a language to make sense of the devastation caused by the Civil War. The essay then turns to two instances of urban destruction: the burning of Columbia, SC, in February 1865 and the New York City draft riots of July 1863. Their representation in the periodical press, as well as in personal and literary accounts, archives the destructiveness of the war even as it shapes its collective memory. While the ashes of Columbia became a climactic episode in the narrative of the Lost Cause, the burning of New York City indexed the problematic memorialization of antistate and anti-Black violence.